Proceed with Caution: Mouse Deep Digit Flexor Tendon Injury Model. Issue 1 (January 2021) - Titan, Ashley L.; Fahy, Evan; Chen, Kellen; Foster, Deshka S.; Bennett-Kennett, Ross; Dauskardt, Reinhold H.; Gurtner, Geoffrey C.; Chang, James; Fox, Paige M.; Longaker, Michael T.
Abstract : Background: The purpose of this study was to determine the feasibility of using mouse models for translational study of flexor tendon repair and reconstruction. Methods: Quantitative data detailing the gross anatomy, biomechanical characteristics, and microscopic structure of the deep digit flexor tendon (DDF) of the mouse hindpaw were obtained. Histological characterization of the DDF and the anatomy of the digit in the mouse hindpaw are detailed. Biomechanical testing determined the load-to-failure, stress, elastic modulus, and the site of tendon failure. Results: In gross anatomy, the origins and insertions of the mouse deep digit flexor tendon are similar to those of the human digit, surrounded by a synovial sheath that is only 1- to 2-cells thick. A neurovascular network runs on each side of the digit outside the synovial sheath, but does not clearly penetrate it. The thickness of the DDF is 0.14 ± 0.03 mm and the width is 0.3 ± 0.03 mm. The thickness of the DDF is less than that of 9-0 nylon needle. The mean failure force of the deep flexor tendon was 2.79 ± 0.53N. Conclusions: The gross anatomy of the mouse hindpaw digit is similar to that of the human digit except for key differences seen in the synovial sheath and vascular supply. The dimensions of the mouse DDF make it challenging to create a clinically translatable repair model using currently available surgical techniques. Despite the similarities between the human and mouse anatomy, and the powerful basic science tools available in murine models, mice are an unreliable model for assessing flexor tendon injury and repair. Abstract : Supplemental Digital Content is available in the text.